2019
DOI: 10.1111/jerd.12552
|View full text |Cite
|
Sign up to set email alerts
|

Does the application of surface treatments in different sintering stages affect flexural strength and optical properties of zirconia?

Abstract: Objective: To investigate the influence of surface treatments conducted in presintering and postsintering stages on flexural strength and optical properties of zirconia.Materials and methods: Specimens were milled from partially sintered zirconia blocks in different geometries and divided into three main groups as presintered, postsintered, and control groups. Test groups were further divided into three subgroups (n = 10) according to the surface treatments conducted (grinding, Er,Cr:YSGG laser irradiation, ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 55 publications
1
15
1
Order By: Relevance
“…The reason for the increased roughness may be highly dependent on the soft structure of the non‐sintered material. The observed microscopy images showed similar features to those published by Kurtulmus‐Yilmaz et al, 29 who stated that the BS group exhibited dramatically lower flexural strength values compared with the control. Passos et al 26 declared that air‐abrasion of Y‐TZP with 50‐ or 110‐μm Al 2 O 3 before sintering should not be preferred because this soft material might be visibly damaged.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The reason for the increased roughness may be highly dependent on the soft structure of the non‐sintered material. The observed microscopy images showed similar features to those published by Kurtulmus‐Yilmaz et al, 29 who stated that the BS group exhibited dramatically lower flexural strength values compared with the control. Passos et al 26 declared that air‐abrasion of Y‐TZP with 50‐ or 110‐μm Al 2 O 3 before sintering should not be preferred because this soft material might be visibly damaged.…”
Section: Discussionsupporting
confidence: 87%
“…Some studies have focused on the effects of sintering and air‐abrasion order 13,25‐29 . Moon et al 25 stated that although air‐abrasion of zirconia at pre‐sintered stage created blunt and melted‐round surfaces, the similar process applied after sintering generated coarse and needle‐like defects, which may trigger crack propagation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, several studies have focused on the sintering/surface treatment order. 10,[27][28][29][30][31][32] Applying pre-treatments in different sintering stages may lead to markedly different surface textures, 27,29 which may enhance both surface roughness and resin bond strength. 31 Previous studies concluded that higher surface roughness values could be obtained with lower m-phase levels by applying air-abrasion before sintering.…”
mentioning
confidence: 99%